Resistance change in on-chip aluminum interconnects under cyclic thermo-mechanical stress. (September 2019) - Ritter, Matthias; Pfost, Martin
Abstract: On-chip metallization, especially in modern integrated BCD technologies, is often subject to high current densities and pronounced temperature cycles due to heat dissipation from power switches like LDMOS transistors. This paper continues the work on a sensor concept where small sense lines are embedded in the metallization layers above the active area of a switching LDMOS transistor. The sensors show a significant resistance change that correlates with the number of power cycles. Furthermore, influences of sense line layer, geometry and the dissipated energy are shown. In this paper, the focus lies on a more detailed analysis of the observed change in sense line resistance.